AFLP MARKER IN GENETIC DIVERSITYASSESSMENT OF FIG (Ficus carica L.) POPULATIONS IN KURDISTAN REGION – IRAQ. - & Jubrael, Hussein (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
In this study, the genetic relatedness of 12 cultivars of fig from different populations in Kurdistan region- Iraq were analyzed using eleven AFLP primers pairs combinations by using the technology of molecular analysis the DNA. Genetic similarity matrices were produced for the AFLP data to calculate genetic distances among their cultivars. Genetic similarity coefficient ranged from 0.1261 to 0.3905. The lowest genetic similarity was observed between Kola and Gala Zard (0.1261). The Hejeera Rash and Shela cultivars were most similar ones with a coefficient of 0.3905. Clustering based on AFLP data for the 12 fig cultivars was identified at the 0.32 similarity level. In the developed dendogram two main groups were found, the first one combined Ketek and Shela together, while the second group contained two sub group Shingaly and Benatty combined together, while in the other sub group cluster three other sub-group were identified. The results of this study may help in the formulation of appropriate strategies for conservation and cultivar improvement in figs, for which limited knowledge of the genetic diversity is available.